Inovasi Produk Untuk Meningkatkan Omzet Penjualan Pada Usaha Mikro Kue Tradisional “ Puji Lestari “ Di Menur Pumpungan Surabaya - Kunto Inggit Gunawan; Mataji Mataji; Sigit Santoso (Pusat Riset dan Inovasi Nasional, 2024)
Since the implementation of the ASEAN Economic Community (AEC) at the end of 2015, it should encourage all economic actors, including SMEs and Micro Enterprises, to improve themselves in order to improve the quality of production of both goods and services. If this is not done, then Indonesia will be an